The Effects of Inflation Uncertainty on Economic Growth Rates in Inflation Targeting Emerging Markets - Туна Кёсе; Али Осман Озтоп (Экономика региона)
Since the 2008-09 global financial crisis, both emerging and developed economies have encountered increased economic uncertainty. Despite substantial research on macroeconomic uncertainties, there remains a significant gap in understanding asymmetric causal relationships between inflation uncertainty and economic growth in inflation-targeting emerging markets. This study addresses this gap by exploring both symmetric and asymmetric causality between inflation uncertainty and economic growth in selected countries: Brazil, Bulgaria, Czech Republic, Greece, India, Korea, Mexico, Russia, and Türkiye. Asymmetric causality tests are crucial as they offer a more nuanced view of how inflation uncertainty and economic growth impact each other in distinct ways, which is vital for enhancing macroeconomic stability and policy effectiveness. The research employs the ARMA-GARCH model to estimate inflation uncertainty and applies both symmetric and asymmetric causality tests. The findings reveal a unidirectional causality from inflation uncertainty to economic growth in Brazil and Bulgaria, and from economic growth to inflation uncertainty in Russia and Türkiye. Furthermore, asymmetric shock analysis shows that negative shocks in inflation uncertainty lead to negative shocks in economic growth in Russia and Korea, while positive shocks in inflation uncertainty correspond with positive shocks in economic growth in India. These insights can help policymakers in emerging markets develop more effective monetary policies. Future research should include a broader range of countries and additional macroeconomic variables to validate these findings and explore inflation uncertainty dynamics further.